Benefits and risks arising from the existence of the structure of the safety net on the example of Poland - Joanna Agnieszka Garbowska (Фінансово-кредитна діяльність: проблеми теорії та практики, 2014)
Changes taking place in the financial sector within the last decades significantly affected the safety of its operations. These changes have increased the impact of any potential crisis on the national economy. Thus the activity of the financial sector is subject to specific supervision of the state. An entire structure of safety net was created to stabilize the financial system. The aim of the network is to reduce the risks associated with the operation of the financial sector which includes i.e. system risk. In the article the risks related to the functioning of the financial sector were discussed, as well as the institutional structure of safety net on the example of Poland, and risks which may arise from the operations of the presented structure. Also the rules limiting the impact of the existence of the institutional safety net structure on the negative phenomena occurring on the financial market were presented.